The Impact of the Greenhouse Education Program on Strengthening Aranding agrocomplex at PT. Natural Nusantara - Sari, Devi Linda; Setiyani, Rahmawati; Rahyunanto, Setyo (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Study This aims to analyze implementation of educational programs House glass at PT. Natural Nusantara as an effort improvement understanding and skills power Work at a time strengthening product branding strategy agrocomplex . Educational program House glass is one of the innovation company in introduce technology modern, environmentally friendly agriculture environment , and empowered competitive method? the research used is descriptive quantitative with techniques data collection through distribution questionnaire to 20 respondents consisting of from employee House glass , staff , and energy technical company . The data obtained analyzed use percentage to find out the extent to which the program has been implemented in a way effective . Research results show that implementation of educational programs House glass has going well , marked by involvement? active participants , suitability material with needs , and its contribution to improvement knowledge and understanding participant to technology House glass . Thus , the implementation of the education program House glass No only impact on increasing capacity source Power humans , but also an important strategy in product branding strengthening PT. Natural Nusantara agrocomplex .